COMBATING CORRUPTION OFFENCES - NISTOR, Iulia Elena; POROF, Alexandru (International Journal of Legal and Social Order, 2022)
Corruption remains a challenge at national and regional levels. This phenomenon affects society in the most diverse ways, being likely to generate negative consequences both in the economic and social life of citizens. At the level of the European Union, it is estimated that the phenomenon of corruption generates costs for the European community in the amount of 120 billion EURO, and over 69% of European citizens consider corruption unacceptable.